2011
DOI: 10.1123/ijspp.6.3.396
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum and Salivary Cortisol Levels in Response to Different Intensities of Exercise

Abstract: Purpose:The effect of exercise intensity on the tracking of serum and salivary cortisol responses was examined in 12 endurance-trained males (maximal oxygen uptake [VO2max] = 58.2 ± 6.4 mL/kg/min).Methods:Subjects rested for 30 min (control) and exercised on a cycle ergometer for 30 min at 40% (low), 60% (moderate), and 80% (high intensity) of VO2max on separate days. Serum and saliva samples were collected pretrial, immediately posttrial, and 30 min into the recovery period from each trial.Results:Cortisol re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 18 publications
9
79
1
4
Order By: Relevance
“…Although, the levels of enzymes and antibacterial compounds are far lower in saliva than blood samples (Papacosta and Nassis 2011), these levels are closely correlated (Cadore et al 2008;Tanner et al 2014;VanBruggen et al 2011). Thus, sIgA and sAA activity can be determined frequently without interfering with the training and daily routine of the athletes (Gatti and De Palo 2011;Papacosta and Nassis 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Although, the levels of enzymes and antibacterial compounds are far lower in saliva than blood samples (Papacosta and Nassis 2011), these levels are closely correlated (Cadore et al 2008;Tanner et al 2014;VanBruggen et al 2011). Thus, sIgA and sAA activity can be determined frequently without interfering with the training and daily routine of the athletes (Gatti and De Palo 2011;Papacosta and Nassis 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Previously studies have reported that during bouts of intense exercise the adrenal cortex secretes high concentrations of cortisol above the CBG binding point (14,15) . Furthermore, cortisol is commonly known for being elevated during times of psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol is most likely the chief hormone that increases the breakdown of fat depositions in response to the physical stress during exercise 9 . However, too much cortisol can also induce the distress as after a certain limit, it begins to catabolize the proteins from the muscles 10 .…”
Section: Discussionmentioning
confidence: 99%